Comparative efficacy of five traditional Chinese medicine injections for treating heart failure with reduced and mildly reduced ejection fraction: Bayesian network meta-analysis - Yu Zheng; Huizhen Zheng; Zhihua Guo (Heliyon, 2024)
Background: More than half of all heart failure (HF) patients have heart failure with reduced ejection fraction (HFrEF) or mildly reduced ejection fraction (HFmrEF). The combination of traditional Chinese medicine injections (TCMIs) with Western medicine treatment (WMT) has been reported to have better efficacy than using WMT alone. However, the positive effects of TCMIs combined with WMT on HFrEF and HFmrEF require more comprehensive and systematic evidence and warrant further investigation. Methods: The NMA searched eight databases, including four English and four Chinese, from database creation to November 10, 2022. We used the Cochrane Risk of Bias tool (ROB 2) to assess the selected studies' quality. OpenBUGS and STATA 17.0 were used for network meta-analysis. Results: The 101 RCTs were included in the systematic review. Studies have shown that when combined with any of the five TCMIs, WMT was more efficient than WMT alone. Shenmai injection (SMI) + WMT may be the best treatment for clinical effectiveness rate (CER) improvement and b-type natriuretic peptide (BNP) reduction. Huangqi injection (HQI) + WMT was the best treatment for improving left ventricular ejection fraction (LVEF). Danhong injection (DHI) + WMT may be the best treatment for lowering left ventricular end-diastolic dimension (LVEDD). Xinmailong injection (XMLI) + WMT was likely the best treatment for increasing the 6-min walking test (6MWT). In addition, XMLI had the lowest incidence of adverse reactions (3.38%). Conclusions: Shenfu injection (SFI), SMI, DHI, XMLI, and HQI combined with WMT have stronger efficiency in treating HFrEF and HFmrEF. However, as all studies were conducted in China, this review is limited by the inevitable selection bias, and further high-quality multicenter randomized controlled trials (RCTs) are required.